AML1-ETO requires enhanced C/D box snoRNA/RNP formation to induce self-renewal and leukaemia - Zhou, Fengbiao; Liu, Yi; Rohde, Christian; Pauli, Cornelius; Gerloff, Dennis; Köhn, Marcel; Misiak, Danny; Bäumer, Nicole; Cui, Chunhong; Göllner, Stefanie; Oellerich, Thomas; Serve, Hubert; et al. (Nature cell biology, 2017)
Leukaemogenesis requires enhanced self-renewal, which is induced by oncogenes. The underlying molecular mechanisms remain incompletely understood. Here, we identified C/D box snoRNAs and rRNA 2′-O-methylation as critical determinants of leukaemic stem cell activity. Leukaemogenesis by AML1-ETO required expression of the groucho-related amino-terminal enhancer of split (AES). AES functioned by inducing snoRNA/RNP formation via interaction with the RNA helicase DDX21. Similarly, global loss of C/D box snoRNAs with concomitant loss of rRNA 2′-O-methylation resulted in decreased leukaemia self-renewal potential. Genomic deletion of either C/D box snoRNA SNORD14D or SNORD35A suppressed clonogenic potential of leukaemia cells in vitro and delayed leukaemogenesis in vivo. We further showed that AML1-ETO9a, MYC and MLL-AF9 all enhanced snoRNA formation. Expression levels of C/D box snoRNAs in AML patients correlated closely with in vivo frequency of leukaemic stem cells. Collectively, these findings indicate that induction of C/D box snoRNA/RNP function constitutes an important pathway in leukaemogenesis.